Local Wisdom and Farmer Welfare through the Nyadran Tradition: A Case Study in Panjang Village - Mutahar, Abdul Kholik; Cahyono, Edi Dwi; Fahriyah, Fahriyah (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
In the era of globalization, the Nyadran tradition is facing challenges, with the understanding of its essence and significance eroding among the community. Some groups are beginning to question the relevance and value of this tradition. Therefore, the objective of this research is to deeply analyze the local wisdom values within the Nyadran tradition and how this tradition can contribute to the well-being of farmers in the village of Panjang. This research is qualitative research combining a case study approach and an ethnographic approach. Primary data was collected through interviews and documentation. This study reveals that the Nyadran tradition in the village of Panjang contains strong local wisdom values that significantly contribute to the well-being of farmers and the community through strengthening social bonds, preserving cultural identity, and adapting to changing times. The Nyadran tradition in the village of Panjang is a cultural treasure that strengthens community solidarity, preserves local values, remains relevant in the face of social change, and makes a positive contribution to the well-being of the community.